2001
DOI: 10.1081/css-120000384
|View full text |Cite
|
Sign up to set email alerts
|

Response of upland rice to fertilizer phosphorus and its residual value in an ultisol

Abstract: An effective and economically efficient phosphorus (P) management strategy requires accounting for the residual value of P fertilizer. Despite a great deal of research on soil P much remains unknown about the residual value of fertilizer P to upland rice in the humid tropics of Africa. A field experiment was conducted for six years (1993 -1998) to determine the response of four promising upland rice cultivars to fertilizer P applied at 0, 45, 90, 135, and 180 kg P ha 21 as triple superphosphate (TSP) only onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 11 publications
3
17
0
4
Order By: Relevance
“…By 1995, Bray 1 P had fallen below the critical SAHRAWAT AND SIKA 330 ORDER REPRINTS range levels (12 to 15 mg Bray 1 P kg soil 21 ) in the soil (4) and this clearly coincided with the decline in grain yields of the rice cultivars (3). The total amounts of P removed in the biomass of five crops varied from 12.6 to 20.8 kg P ha 21 and the apparent recovery of applied P was low and varied from 4.8 to 11.0% of the applied fertilizer P. The data on P removal by rice crops suggest that a greater of the applied P fertilizer was removed by chemical processes in the soil.…”
Section: Possible Causes Of Decline In Bray 1 Pmentioning
confidence: 98%
See 1 more Smart Citation
“…By 1995, Bray 1 P had fallen below the critical SAHRAWAT AND SIKA 330 ORDER REPRINTS range levels (12 to 15 mg Bray 1 P kg soil 21 ) in the soil (4) and this clearly coincided with the decline in grain yields of the rice cultivars (3). The total amounts of P removed in the biomass of five crops varied from 12.6 to 20.8 kg P ha 21 and the apparent recovery of applied P was low and varied from 4.8 to 11.0% of the applied fertilizer P. The data on P removal by rice crops suggest that a greater of the applied P fertilizer was removed by chemical processes in the soil.…”
Section: Possible Causes Of Decline In Bray 1 Pmentioning
confidence: 98%
“…Phosphorus-efficient upland rice cultivars, adapted to acid soil conditions have been identified and evaluated for their P responsiveness and P efficiency in annual and long-term P experiments (1,2,3). Phosphorus (P) deficiency has been identified as the major constraint to rice production on these soils (1).…”
Section: Introductionmentioning
confidence: 99%
“…Such information however can provide useful leads for developing P management strategies. [7] Results showed that there was a rapid loss of available P in the Ultisol [7] because of its fixation by sesqui-oxides. Under these conditions, a combination of P-efficient genotypes and improved P management strategy is more practical for achieving sustainable crop production for crops such as upland rice.…”
Section: Introductionmentioning
confidence: 99%
“…Ce constat est accentue´dans les syste`mes de production intensive du riz (Sahrawat et al 2001) et illustre les limites de l'effet de la fertilisation phosphate´e sur les varie´te´s de riz d'origine asiatique couramment cultive´es sur ces sols . Une telle situation favorise la pratique de l'agriculture itine´rante qui est a`la base de la de´forestation et des de´se´quilibres e´cologiques, phe´nom-e`nes qui menacent la durabilite´de l'agriculture.…”
unclassified